Food & feeding habits of an endemic carp, Osteobrama belangeri (Val.) in Manipur - Basudha, Ch; Viswanath, W (Indian Journal of Fisheries, 2011)
A total of 146 O. belangeri (V) of total length 6.0-25.9 cm and age group 0*to 4* year were sampled from different water sources. Their gut contents wereanalysed and buccopharynx studied. The percentage composition of major fooditems in various size groups of fish was different. In juveniles (6.-10 cm TL)zooplankton contents were the highest (51.9 %). Aquatic plants formed themain food item (40-60 %) in grownup fishes (10-26) cm TL). The alimentarycanal is a long tube with undifferentiated stomach. The development ofmassive pharyngeal teeth reveals the capability of crushing hard bodied preys